Whistleblowing Intentions in Balinese Government Institutions: A Cultural and Phenomenological Perspective - Wiradharma, Gde Wisnu; Sudarma, Made; Amirya, Mirna (Universitas Pendidikan Ganesha, 2025)
The whistleblowing system is a mechanism for reporting suspected acts of fraud that have occurred, are ongoing, or are anticipated to occur, involving employees and other parties associated with suspected acts of fraud within the organization where they work. In this context, culture plays a significant role in influencing an individual's intention to act as a whistleblower. This study aims to identify the cultural factors that predominantly influence whistleblowing intentions. The research was conducted in government institutions in Bali, considering that the cultural values of Tat Twam Asi and Koh Ngomong are integral to Balinese culture. The selected institutions were the Bali Provincial Office of the Ministry of Religious Affairs and the Faculty of Economics and Business at Udayana University, as both institutions have received WBK (Corruption-Free Zone) and WBBM (Clean and Service-Oriented Bureaucratic Zone) awards. This study employs an interpretive paradigm to understand the dominant cultural influences on whistleblowing intentions. It is qualitative research that applies phenomenology as its methodology and research method. Data were collected from sources such as in-depth interviews, documentation, and observations of employee activities within the institutions. The data were then contextually explained to facilitate interpretation. The findings reveal that societal culture significantly influences whistleblowing intentions. In general, the Tat Twam Asi culture is more supportive of reporting violations compared to the Koh Ngomong culture. People in Bali tend to report violations to enhance reputation and protect the organization rather than remain silent and reluctant to disclose misconduct.